Intermediarne strukture in družbeni sistem znanosti - Mali, Franc (Družboslovne razprave, 1998)
In the first part of the article the author deals with the problems of intermediary structures in the context of the general systemic theoretical concept of functional differentiation and integration. His main thesis is that the modern evolutionary concepts developed in the context of systemic social theory consider the reflexive dimension as the most important dimension in the inter-systemic relations. The practical cases of university-industry-government relations on the way of the triple helix show on increasing role of the reflexive dimension in the code of political communications. The reflexive dimension unavoidably adds to a higher degree of freedom in the decision-making processes. At the same time, it reduces the degree of social risk, which is the result of a dynamic and non-linear scientific and technological development. In the second part of the article, attention is given to the concrete analysis of the scientific (research) councils. The research councels are the institutions, where the intermediary negotation systems have the longest tradition.
Keywords: družba; society; družbena diferenciacija; družbeni sistemi; science; znanost; teorija sistemov